EXPLORING THE POTENTIAL ENERGY OF LODAGUNG MINI-HYDROPOWER PLANT IN BLITAR, WEST JAVA, INDONESIA - Etty Susilowati; Raymond Valiant Ruritan (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2021)
Renewable energy in Indonesia is not optimally developed. Most existing renewable energy power plants come from water and geothermal, but the utilized capacity is far away from significant. Lodagung mini-hydro power plant was built by The Public Corporation, Jasa Tirta I with an installed capacity of 2x650 kW utilizing water from the Lodagung Irrigation Channel, Wlingi Dam to generate electricity in Blitar Regency, East Java. The plant has become the first to use Siphon technology in its operation. This study aims to analyse the potential power generated by Lodagung Mini-hydropower plant using primary and secondary data. The data processing was done by calculating the reliable discharge of the irrigation channel for three years since 2011 to 2013; calculating the water discharge in the siphon pipe; and calculating the estimated power generated by the plant. The findings indicate that the maximum discharge of the Lodagung irrigation channel is 13.78 m3/second, and the minimum discharge is 8.89 m3/second. The design discharge is 13.78 m3/second, and the maximum discharge in the siphon pipe is 3.96 m3/second/pipe. Based on the need, the expected power generated ranges from 16.48 kWh/day to 28.66 kWh/day.